2004
DOI: 10.1002/mrd.20173
|View full text |Cite
|
Sign up to set email alerts
|

Several signaling pathways are involved in the control of cattle oocyte maturation

Abstract: The main limit of in vitro production of domestic mammal embryos comes from the low capacity of in vitro matured oocytes to develop after fertilization. As soon as they are separated from follicular environment, oocytes spontaneously resume meiosis without completion of their terminal differentiation. Roscovitine (ROS), an inhibitor of M-phase promoting factor (MPF) kinase activity reversibly blocks the meiotic resumption in vitro. However, in cattle maturing oocytes several cellular events such as protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…It should be mentioned here that this result is not in agreement with observations made by Vigneron et al (2004b). These authors reported no or only very low abundance of Akt in the GV stage (time 0) of bovine oocytes.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…It should be mentioned here that this result is not in agreement with observations made by Vigneron et al (2004b). These authors reported no or only very low abundance of Akt in the GV stage (time 0) of bovine oocytes.…”
Section: Discussioncontrasting
confidence: 83%
“…It was previously shown that another kinase named Akt (protein kinase B; PKB) is also abundant in mouse and bovine oocytes (Hoshino et al 2004, Vigneron et al 2004a, 2004b. The results reported indicate that Akt is likely to participate in the maturation of oocytes, probably independent of MPF activation.…”
Section: Introductionmentioning
confidence: 86%
“…MAPK1 and MAPK3 (also known as ERK2 and ERK1 respectively) and maturation promoting factor (MPF), a complex of cyclin B1 and cell-cycle controller p34 kinase cyclindependent kinase 1 (CDK1) constituted the main signalling pathways of oocyte maturation control (see review (Liang et al 2007)). We showed previously that several protein kinases are differentially activated in bovine oocytes during IVM: MAPK3/MAPK1, jun N-terminal kinase (JNK), AKT, Aurora kinases (Vigneron et al 2004a, 2004b, Uzbekova et al 2008 and AMPactivated protein kinase (AMPK; Tosca et al 2007). Another member of MAPK super-family, MAPK14 (alias p38) was expressed in porcine cumulus-oocyte complexes (COCs) and its activation varied during IVM (Villa-Diaz & Miyano 2004).…”
Section: Introductionmentioning
confidence: 99%
“…JNK signaling is also involved in controlling oocyte development in other vertebrates (Vigneron et al, 2004;Browaeys-Poly et al, 2005). Our previous studies indicated that the expression of the jnk1 gene displays distinct patterns during the sex reversal of the rice-field eel M. albus, which has some typical features of natural sexual reversal during its lifecycle (Xiao, 1995;Xiao and Liu, 1995;Xiao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%